AL-DARURIYAT AL KHAMS DALAM TINDAK PIDANA PENCURIAN: (ANALISIS PUTUSAN DI PENGADILAN NEGERI PINRANG) - Saidah, Saidah; Rafid A, Noercholis; Syatar, Abdul (Fakultas Syariah Institut Agama Islam Negeri Palu, 2020)
This study discusses al-Daru>riya>t al-Khams in the Crime of Theft (Verdict Analysis in Pinrang District Court). It is the aim of this study to reveal the relationship between al-daru riyat al-khams and the verdict of criminal sanction of theft in Pinrang District Court. The implication of this study is that the Pinrang District Court verdict has considered aspects of al-daru riyat al-khams regarding assets’ safeguarding in terms of the theft case. The judge decided the case by prioritizing proven divine values by mentioning for the sake of justice based on that one godhead (Believe in the one and only God). Imposing sanctions by the judge is by taking into account the burdensome and mitigating elements for the benefit of the defendant.",